Thrombolysis with rt-PA for an ischemic stroke in boy treated with Fontan operation - Bianco, Mariangela; Simionato, Franco; Giusti, Cristina; Corea, Francesco; Giua, Alessandra; Martinelli, Vittorio; Comi, Giancarlo; Sessa, Maria (Journal of Pediatric Neurology, 2011)
We first report the case of a 14-year-old boy, previously treated with a modified Fontan operation at the age of 2, who underwent an intra-arterial thrombolysis for an ischemic stroke with a favorable outcome. No controlled randomized trials on thrombolysis among childhood stroke have been conducted yet. This and other similar cases suggest that thrombolysis may also be safe and beneficial in pediatric patients and those cases may benefit from a prompt access to specialized stroke centers.
Keywords: Ischemic stroke; Fontan operation; thrombolysis; recombinant tissue plasminogen activator